Aerodynamics of voice of hearing impaired - Salaj Bhatnagar (Journal of All India Institute of Speech and Hearing)
The present study was conducted to find out the difference among the aerodynamic features in normal hearing subjects and that of the hearingimpaired subject. The parameter selected for this study were, (a) vital capacity, (b) peakflow, (c) maximum sustain duration, (d) vocal efficiency. In total there were 80 subjects taken for the study of which 40 were adult hearing-impaired 20 male and 20 female. The second set of population ie. next 40 subjects were normal hearing subjects, 20 males and 20 females.